PELATIHAN DAN SOSIALISASI PEMASANGAN PERANGKAP ATRAKTAN BAGI PETANI UNTUK MENGENDALIKAN HAMA PENGGEREK BUAH KOPI - Warlinson Girsang; Irawaty Rosalin; Rudiyantono Rudiyantono; Ahmad Husin; Yogie Nasution; Rio Pradana Muliyandra; Surya Nainggolan (Jurnal Pengabdian Masyarakat Sapangambei Manoktok Hitei, 2022)
In Simalungun regency, the intensity of the coffee berry borer attack was in the category of heavy and very heavy attack. The high intensity of attacks is caused by coffee farmers not carrying out control efforts. As a result, the population and spread of the coffee berry borer has increased over time. The majority of coffee farmers do not know the control technology to overcome the coffee berry borer. Including pest control using attractant traps, coffee farmers in Simalungun Regency are still not familiar with it. The way the attractant works, which produces an aroma that is able to stimulate female coffee berry borer pests to approach and then enter the trap, is completely unknown to coffee farmers. For the introduction of this pest control technology, the activities carried out with partner farmers started from providing counseling on pest control methods, introducing attractants and how they work, training farmers through demonstrations of installing attractants in coffee plantations, as well as socializing the importance of all coffee farmers willing to install attractants in their respective gardens. The results of the training and socialization of trapping attractants showed positive success benefits, as reflected in the knowledge of partner farmers on pre-test questions (before training) and answers to post-test questions (after training was given several times). Farmers' responses in the discussion session also reflected more curiosity about the use of attractants to overcome losses caused by the coffee berry borer.